Pengaruh Keterampilan Kolase Cobek terhadap Kemampuan Motorik Halus Anak Kelompok B TK Nusa Indah Bedingin, Sugio, Lamongan - Dhetty Eko Dianita Sari; Aisyah, Aisyah (CV. ULIL ALBAB CORP, 2025)
Early childhood, an important period in a child's physical and mental development. This study aims to determine the effect of cobek collage skills on the fine motor skills of group B children at Nusa Indah Bedingin Kindergarten, Sugio, Lamongan in the 2024-2025 school year. Collage activities as a learning medium to improve hand and eye coordination, as well as children's fine motor skills. This study uses a pseudo-experimental design with a pretest-posttest control group design approach. The subjects were 17 children into two groups, namely the experimental group that carried out the cobek collage activity and the control group that was not given the treatment, with observation and documentation, and analyzed the t-test. The study showed that there was a significant improvement in children's fine motor skills after being given the cotoral collage treatment, with a value of t = -19.134 and p < 0.001. These results indicate that the cobek collage activity is effective in stimulating children's fine motor skills, such as holding, sticking, and arranging materials. Research suggests integrating cobek collages in kindergarten learning to support children's fine motor development.